Grain growth rate, canopy temperature depression, chlorophyll content and AGPase activity in relation to grain yield in spring wheat genotypes under late sown condition - Baral, Sagari; Chhabra, Ashok Kumar; Behl, Rishi Kumar; Sikka, Virendra Kumar; Bishnoi, Om Prakash; Munjal, Renu (Journal of Cereal Research, 2013)
Twenty four (24) wheat genotypes were grown in 3 meter long two row plots in randomized block design with three replications at CCS Haryana Agricultural University, Hisar, Research Farm under two natural photothermal environments created through alteration of dates of sowing i.e. 13th November 2007(Normal sown, NS) and 3rdJanuary 2008 (Late sown,LS). These genotypes were evaluated for genotypic variation for canopy temperature depression (CTD, 0C), grain growth rate at three intervals (GGR1-3, mg/day/grain) and grain yield (GY, g/plant). Out of these, six genotypes were selected based upon their early (WH 1070 and WH 1021), medium (WH1071and WH1066) and late (WH1057 and DBW16) flag leaf senescence. These six genotypes were used to study parameters like their AGPase activity (nmol.mg-1.min-1) and chlorophyll content ((Î¼ mol g-1fresh weight ) at 28 days after anthesis; in addition to grain growth rate. Significant genotypic variations under different dates of sowing for GGR1-3, GY and CTD were recorded. Significant positive correlation between GY and GGR3 under normal as well as late sown conditions was noticed. Two stay green genotypes WH1057 and DBW16 had higher chlorophyll content and grain growth rate (GGR3) in late sown conditions as compared to other genotypes. The CTD, GGR3, and AGPase at 28 days showed positive correlation with grain yield under late sown conditions. Thus CTD, grain growth rate and AGPase activity could be used as selection criteria for yield improvementunder late sown conditions.